Case study: Impact of inter- and intra-day energy parameters on bone health, menstrual function, and hormones in an elite junior female triathlete - Vescovi, J. D.; VanHeest, J. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
This observational case study examined the association of inter- and intraday energy intake and exercise energy expenditure with bone health, menstrual status and hematological factors in a female triathlete. The study spanned 7 months whereby energy intake and exercise energy expenditure were monitored three times (13 d); 16 blood samples were taken, urinary hormones were assessed for 3 months, and bone mineral density was measured twice. Energy availability tended to be sustained below 30 kcal/kg FFM/d and intraday energy intake patterns were often "back-loaded" with approximately 46% of energy consumed after 6 p.m. Most triiodothyronine values were low (1.1-1.2nmol/L) and supportive of reduced energy availability. The athlete had suppressed estradiol (105.1 ± 71.7pmol/L) and progesterone (1.79 ±1.19nmol/L) concentrations as well as urinary sex-steroid metabolites during the entire monitoring period. Lumbar spine (L1-L4) bone mineral density was low (age-matched Z-score -1.4 to -1.5). Despite these health related maladies the athlete was able to perform typical weekly training loads (swim: 30-40 km, bike: 120-300 km, run 45-70 km) and was competitive as indicated by her continued improvement in ITU World Ranking during and beyond the assessment period. There is a delicate balance between health and performance that can become blurred especially for endurance athletes. Education (athletes, coaches, parents) and continued monitoring of specific indicators will enable evidence-based recommendations to be provided and help reduced the risk of health related issues while maximizing performance gains. Future research needs to longitudinally examine how performance on standardized tests in each discipline (e.g., 800-m swim, 20-km time trial, 5-km run) is impacted when aspects of the female athlete triad are present.